Investigating the anatomical relationship between the maxillary molars and the sinus floor in a Chinese population using cone-beam computed tomography - Xi Zhang; Yan Li; Yi Zhang; Fengling Hu; Bin Xu; Xiaojun Shi; Liang Song (BMC, 2019)
Abstract Background The anatomical relationship between the root apices of maxillary molars and the maxillary sinus floor (MSF) is important for the treatment of dental implantations and endodontic procedures. In this study, the detailed anatomical relationships between the root apices of maxillary molars and the MSF were studied in a Chinese population using CBCT. Methods We collected the CBCT data files of patients who visited the stomatology outpatient clinic in Shanghai Fifth People's Hospital, Fudan University from January 1, 2017 to January 1, 2019 and measured the following items: the distance between the molar root apices and the MSF, the thickness of the mucosa and cortical bone of the MSF closest to the root apices, and the angle between the buccal and palatal roots. Results The shortest distances between the root apices and the MSF were 1.57 ± 3.33 mm (the mesiobuccal root of the left second molar) and 1.61 ± 3.37 mm (the mesiobuccal root of the right second molar). Apical protrusion over the inferior wall of the sinus most often occurred in the mesiobuccal root of left second molar (frequency, 20.5%). The mucosa of the MSF was thinnest at the distobuccal root of the right second molar (1.52 ± 0.85 mm), the cortical bone of the MSF was thinnest at the mesiobuccal root of the right second molar (0.46 ± 0.28 mm), and the angle between the buccal and palatal roots ranged from 12.01° to 124.2° (42.36 ± 24.33 °). Conclusions Among the root apices of the maxillary molars, the mesiobuccal root apex of the left second molar was closest to the MSF, and it had the highest incidence of protrusion into the sinus. The unique anatomical relationship between the maxillary molars and the MSF in this Chinese population is critical for treatment planning for dental implantation or endodontic procedures.